PENGARUH MEDIA BUSY BOOK TENTANG KARIES GIGI TERHADAP PENGETAHUAN KARIES GIGI PADA ANAK SEKOLAH DASAR - Azhari, Adina Ridha; Haryani, Wiworo; Almujadi, Almujadi (Poltekkes Kemenkes Yogyakarta, 2021)
Preliminary studies conducted each of 10 students found 80% in SDN 1 Bumirejo Wonosobo and 70% in SDN 1 Pungangan Wonosobo did not understand the knowledge of dental caries. From the results of dental and oral examination at SDN 1 Bumirejo Wonosobo and SDN 1 Pungangan Wonosobo 70% of students have dental caries. To knowing the influence of the Busy Book on dental caries on dental caries knowledge in elementary school children. This research is quasi experiment with non equivalent control group design. The population is the fourth grade of elementary school children in SDN 1 Bumirejo Wonosobo and SDN 1 Pungangan Wonosobo. The sample consisted of 56 students aged 10-11 years, 28 students were in the experimental group who were given counseling with the Busy Book media and 28 students were the control group who were given counseling using the lecture method. Data analysis used the Wilcoxon Test to determine the pretest and posttest values ??of dental caries, the Mann-Whitney Test to find out the comparison of dental caries knowledge between the experimental and control groups The difference in the level of knowledge of dental caries in both categories in the experimental group was 53.57% and the control group was 42.85%, the Wilcoxon-Test Test analysis showed differences in the value of p=0.00 (p<0.05). Mann-Whitney analysis shows the mean rank of the experimental group 41.00>16.00 the control group. There is a significant difference between counseling with Busy Book media and counseling using lecture method on the level of dental caries knowledge. Busy Media Books as a media to promote oral health to increase knowledge about dental caries in elementary school students